Survey of Consumer Attitudes and Behavior, April 1990 ([Verlag nicht ermittelbar], 1993)
These surveys were undertaken to measure changes in consumer attitudes and expectations, to understand why these changes occur, and to evaluate how they relate to consumer decisions to save, borrow, or make discretionary purchases. This type of information is essential for forecasting changes in aggregate consumer behavior. Since the late 1940s, these surveys have been produced quarterly through 1977 and monthly thereafter. Each monthly survey probes a different aspect of consumer confidence. Open-ended questions are asked concerning evaluations and expectations about personal finances, employment, price changes, and the national business situation. Additional questions probe buying intentions for automobiles and the respondent's appraisals of present market conditions for purchasing houses, automobiles, and other durables. Demographic information includes ethnic origin, sex, age, and education.